2005
DOI: 10.1007/s10974-005-7004-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Expression Profiles in Prenatal Pigs in Relation to Myogenesis

Abstract: Myogenesis, the formation of muscle fibers, is a complex process. Pigs have been selected for efficient muscle growth for the past decades making them interesting to study myogenesis. We studied expression profiles of genes known to affect myogenesis, muscle structural proteins, and energy metabolism in prenatal pigs from 14 to 91 days of gestation. Primary and secondary muscle fiber formation takes place during days 30-60 and 54-90 of gestation, respectively. Differential expression and expression levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 30 publications
5
69
2
Order By: Relevance
“…We studied the transcriptome expression in porcine longissimus dorsi muscles of Duroc pigs. The results showed that especially the primary wave of prenatal muscle fibre formation is strongly genetically regulated, while the secondary muscle fibre formation is associated with much less differential gene expression (te Pas et al, 2005;Cagnazzo et al, 2006). This is in agreement with the fact that the secondary muscle fibre formation can be regulated with feed, while the primary muscle fibre formation cannot be affected Stickland et al, 2004;reviewed in Rehfeldt et al, 2011a, b).…”
Section: Prenatal Muscle Tissue Development Related To Post-mortem Mesupporting
confidence: 77%
See 1 more Smart Citation
“…We studied the transcriptome expression in porcine longissimus dorsi muscles of Duroc pigs. The results showed that especially the primary wave of prenatal muscle fibre formation is strongly genetically regulated, while the secondary muscle fibre formation is associated with much less differential gene expression (te Pas et al, 2005;Cagnazzo et al, 2006). This is in agreement with the fact that the secondary muscle fibre formation can be regulated with feed, while the primary muscle fibre formation cannot be affected Stickland et al, 2004;reviewed in Rehfeldt et al, 2011a, b).…”
Section: Prenatal Muscle Tissue Development Related To Post-mortem Mesupporting
confidence: 77%
“…Interestingly, the number of differently expressed genes for energy metabolism suggest that proliferation of myoblasts prior to differentiation is accompanied by oxidative phosphorylation, while during differentiation (i.e. fusion into multinucleated muscle fibres) glycolysis seems to be of main importance (te Pas et al, 2005).…”
Section: Prenatal Muscle Tissue Development Related To Post-mortem Mementioning
confidence: 99%
“…The mean relative ratios were approximately Expression analyses of muscle genes in different pig breeds and different developmental stages showed to be very useful both to improve gene maps and to increase the number of candidate genes that could be involved in controlling production traits (Wimmers et al, 2004). The macro-and microarray technologies were used to simultaneously measure the expression of a large number of genes in different developmental stages of embryonic/fetal development and in postnatal muscle, as well as to study differences in expression between different breeds of pigs (te Pas et al, 2005;Cagnazzo et al, 2006;Wimmers et al, 2007). It was shown that some genes are down regulated, others up regulated, and some do not change their expression level.…”
Section: Resultsmentioning
confidence: 99%
“…Davoli et al, 2002; te Pas et al, 2005;Cagnazzo et al, 2006). Many of the genes were mapped (Davoli et al, 2002) and some of them were used as functional or positional candidates for association studies with meat quality and carcass traits (Wimmers et al, 2007) or for QTL mapping .…”
mentioning
confidence: 99%
“…Murine tongue muscle displays a distinct developmental profile of MRF gene expression compared with other muscles (Dalrymple et al 1999;Yamane et al 2000). In recent years, MRFs expression profile has been proven to vary among the muscles of different origins (Te Pas et al 2005) and among the different muscle fiber types. Muscle fibers can be divided into two types: redder muscle fiber types and whiter muscle fiber types.…”
Section: Mots Clé S: Canard Myog Et Mrf4 Expression De´veloppementmentioning
confidence: 99%